CARTOGRAPHIC FEATURES EXTRACTION METHODOLOGY IN REMOTE SENSING IMAGES AIMING AT THE CARTOGRAPHIC UPDATE OF ALLOTMENTS - E. S. Nascimento; A. A. L. Ferreira; T. G. Godoy; C. F. M. Fontoura Júnior; G. P. Cardim; P. M. B. D. Pina; E. A. da Silva (ISPRS Annals of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2023)
The need for updated cartographic products in Brazil is essential for effective planning and project implementation. Outdated maps, which can be up to three decades old, hinder various projects, making it necessary to find alternative methods for semi-automated cartographic updates. This study focuses on the use of orbital images obtained through Remote Sensing, processed using Digital Image Processing and Mathematical Morphology techniques. The methodology aims to extract and detect urban targets (allotments) and update an outdated cartographic database. The results obtained demonstrate the achievement of the established objectives, with the proposed methodology outperforming conventional filtering methods. Statistical validation confirms the effectiveness of post-processing techniques such as inpainting. The automated extraction and processing of features using software tools like MATLAB, CARTOMORPH, and QGIS prove to be an efficient solution for updating outdated maps. Ongoing research and refinement of methods aim to enhance the accuracy and reliability of the methodology, making valuable contributions to the cartographic community and benefiting map users worldwide.